Congenital erythropoietic porphyria with hemolytic anemia - Massod Qazi; Hassan Iffat; Khan Dilshad; Sameem Farah; Quadri M; Hussain S; Majid Sabiya (Indian Journal of Dermatology, 2005)
A 15 year old boy with clinical, hematological and biochemical profile of congenital erythropoietic porphyria with hemolytic anemia is being reported in view of the rarity of this condition.